The Payment of Inheritance Acquisition Duty of Right on Land and Building in Sleman - Perwitiningsih Perwitiningsih; Rikardo Simarmata (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2021)
This research is aimed at revealing the collection practice of inheritance Acquisition Duty of Right on Land and Building (BPHTB) of Marital Properties in the form of land rights at Regional Finance and Assets Office (BKAD) Sleman and analyzing the practice based on the inheritance and land law. This research is empirical legal research. The data collected in this research are analyzed using a qualitative method and presented descriptively in order to obtain descriptive qualitative results. The result shows that there has been an overpayment of tax that should not be billed in the collection of BPHTB inheritance in the form of land as the marital property at BKAD Sleman since the living widow’s or widower’s right is counted. Land titles as joint assets, if registered only in the name of the heir without registering the spouse's name, the BKAD Sleman does not take into account the spouse’s right to the land titles. This calculation happens because a land certificate as the marital property is registered only under the name of a husband or a wife alone, and BKAD Sleman interprets this condition as that the owner of the certificate is the one whose name is registered on it.